FDA warning letters about food products : how to avoid or respond to citations - Frestedt, Joy L. (Academic Press, an imprint of Elsevier, 2017)
FDA Warning Letters About Food Products: How to Avoid or Respond to Citations uses examples of FDA warning letters about food products as training tools to discuss important quality and manufacturing issues encountered by food companies around the world as they bring food products into the US market. Focused specifically on FDA warning letters surrounding new dietary ingredients and dietary supplements, the book first introduces FDA warning letters in general. Each chapter then focuses on specific issues identified, including HAACP/quality systems, imports/exports, food contact issues, etc. This book helps the food industry train professional team members (across the spectrum of experience levels) to avoid common issues often cited in warning letters. It serves both as an authoritative reference on the common types of warning letters issued to food companies today, and as a guide to best practices for food manufacturers.